2009
DOI: 10.1016/j.jvs.2008.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of a Kommerell's diverticulum in a patient with a left-sided aortic arch and right-sided descending thoracic aorta

Abstract: Thoracic aortic anomalies are rare and may be associated with pathologic vascular conditions necessitating intervention. We present a case of a patient with a left aortic arch, right descending thoracic aorta, and a Kommerell's diverticulum giving rise to an aberrant right subclavian artery. The Kommerell's diverticulum was successfully managed with a right carotid to subclavian artery bypass and thoracic endograft exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It was said to the average size at aneurysmal rupture was 5.8 cm, but the range was wide which might to be rupture [2,3]. In TEVAR therapy, the presence of the ALSA requires coil embolization to prevent a type II endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…It was said to the average size at aneurysmal rupture was 5.8 cm, but the range was wide which might to be rupture [2,3]. In TEVAR therapy, the presence of the ALSA requires coil embolization to prevent a type II endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature by Cinà et al, the mean size at which these aneurysms rupture was reported to be 5.8 cm, although rupture was observed to have occurred over a wide range of diameters (2-10 cm). 1,3,9,10 Treatment options for an LSA aneurysm include surgical repair, combined (surgical and endovascular) treatment, or total endovascular repair. However, previously published data are limited to a few single case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several congenital anomalies of the aortic arch and great vessels have been extensively described. [1][2][3] Right-sided aorta is present in 0.04% to 0.1% of the population, and 50% of right-sided aortic arches are associated with an aberrant left subclavian artery (LSA). 4 A rare condition called Kommerell's diverticulum (KD), defined as an obviously dilated part of the origin of the aberrant artery from the aorta, may occur in patients with aberrant LSA.…”
mentioning
confidence: 99%
“…The mean size associated with rupture was 5.8 cm in one case series report. 16,17 Another serious complication is embolization. 8…”
Section: Diagnosis Of Kdmentioning
confidence: 99%
“…The patient underwent thoracic aortic endovascular repair (TEVAR) plus use of graft to repair the aberrant subclavian artery. 17…”
Section: Surgical Management Of Kdmentioning
confidence: 99%